Characterisation of three novel β-1, 3 glucanases from the medically important house dust mite Dermatophagoides pteronyssinus (airmid). (December 2019) - Waldron, Rose; McGowan, Jamie; Gordon, Natasha; Mitchell, E. Bruce; Fitzpatrick, David A.; Doyle, Sean
Abstract: The European house dust mite, Dermatophagoides pteronyssinus is a major source of airborne allergens worldwide and is found in half of European homes. Interactions between microbes and house dust mites (HDM) are considered important factors that allow them to persist in the home. Laboratory studies indicate the European HDM, D. pteronyssinus is a mycophagous mite, capable of utilising a variety of fungi for nutrients, however specific mycolytic digestive enzymes are unknown. Our previous work identified a number of putative glycosyl hydrolases present in the predicted proteome of D. pteronyssinus airmid and validated the expression of 42 of these. Of note, three GH16 proteins with predicted β-1, 3 glucanase activity were found to be consistently present in the mite body and excretome. Here, we performed an extensive bioinformatic, proteomic and biochemical study to characterize three-novel β-1, 3 glucanases from this medically important house dust mite. The genes encoding novel β-1, 3 glucanases designated Glu1, Glu2 and Glu3 were identified in D. pteronyssinus airmid, each exhibited more than 59% amino acid identity to one another. These enzymes are encoded by Glu genes present in a tri-gene cluster and protein homologs are found in other acari. The patchy phyletic distribution of Glu proteins means their evolutionary history remains elusive, however horizontal gene transfer cannot be completely excluded. Recombinant Glu1 and Glu2 exhibit hydrolytic activity toward laminarin, pachyman and barley glucan. Excreted β-1, 3 glucanase activity was increased in response to D. pteronyssinus airmid feeding on baker's yeast. Active β-1, 3 glucanases are expressed and excreted in the faeces of D. pteronyssinus airmid indicating they are digestive enzymes capable of breaking down β-1, 3 glucans of fungi present in house dust. Graphical abstract: Image 1 Highlights: β-1, 3 glucanases found in HDMs and other Acari species, specifically those within the Acariformes order. Mycophagous HDM, D. pteronyssinus, increases excretion of β-1, 3 glucanases in response to Saccharomyces cerevisiae diet. β-1, 3 glucanases excreted by D. pteronyssinus are found in house dust.